ECONOMIC MATERIALISM AND ENTREPRENEURIAL INTENTION IN ROMANIAN STUDENTS - Bogdan Ioane MARCULESCU; Laura BRANCU; Diana Claudia SALA (Management & Marketing)
This study intends to analyze the correlation between economic materialism and entrepreneurial intention in a sample of University students from Romania. In addition, the study attempts to identify the particularities of the Romanian culture in regards to materialism and its impact on entrepreneurial intention. Furthermore, the study aims to evaluate the level of economic materialism in Romanian business students. The reliability analysis disclosed a lower inter item correlation in one of the materialism subscales, and the subsequent factor analysis found that two underlying factors account for the majority of the variance. Our result fits with previous research proposing that inconclusive factor analysis results prove that ‘materialism is culturally dependent” (Flynn et al, 2013, p.62). Scales developed in a Western culture should go through a process of cultural adaptation, in addition to the process of back translation, to ensure reliable results. These conclusions are valuable due to the scarcity in research on economic materialism and entrepreneurial intention in Romania.